HIV/AIDS in the countries of the former Soviet Union: societal and attitudinal challenges - Rechel, Bernd (Central European Journal of Public Health, 2010)
For several years, some of the countries of the former Soviet Union have experienced the fastest growing HIV epidemic in the world, with the vast majority of reported infections contracted through injecting drug use. However, most governments of the region have been slow to recognize the severity of the problem. The scope and coverage of governmental HIV/AIDS programmes have remained very limited. Harm reduction programmes are mainly financed by external donors, while substitution treatment remains illegal in Russia and unavailable in some other countries of the region. Being based on a review of published and grey literature, this paper explores attitudinal and societal barriers to scaling up HIV programmes in the countries of the former Soviet Union. A major challenge in many countries is negative public attitudes towards people living with HIV, as well as towards those most at risk of contracting the disease: injecting drug users, sex workers, and men who have sex with men. This extends to the actions of state authorities which often pursue a punitive approach to drug users, with high rates of incarceration for minor drug offences. While many of the findings reported here relate to the Russian Federation, there is reason to believe that similar challenges exist in many other countries of the former Soviet Union. More needs to be done to document challenges to HIV prevention and treatment programmes across the region, so that policy interventions can be more effective.
Keywords: Central and Eastern Europe; Společenství nezávislých států; Humans; Health Knowledge, Attitudes, Practice; Acquired Immunodeficiency Syndrome; Financing, Organized; Health Policy; financování organizované; zdraví - znalosti, postoje, praxe; Substance Abuse, Intravenous; AIDS; HIV/AIDS; Prejudice; discrimination; Commonwealth of Independent States; předsudek; prejudice; lidé; intravenózní abúzus drog; HIV Infections; zdravotní politika; HIV infekce; former Soviet Union